Comparison of efficacy between intravenous clonidine and dexmedetomidine as pre-medication in attenuating hemodynamic stress responses during laparoscopic cholecystectomy - Diptimay Majumder; Susanta Kumar Halder; Swarup Datta; Sruthi Naresh; Soma Chakraborty; Subrata Pahari (Asian Journal of Medical Sciences, 2023)
Background: Laparoscopic cholecystectomy is a commonly performed surgery and stable intraoperative hemodynamic status is desirable during pneumoperitonium. Clonidine and dexmedetomidine (alpha-2 adrenergic agonist) were used in this study to attenuate the stress response of pneumoperitoneum because alpha-2 adrenergic agonists help in the attenuation of neuroendocrine and hemodynamic responses to surgery and anesthesia, due to its sympatholytic action. Aims and Objectives: The aims and objectives of the study are to conduct a comparative evaluation of clonidine and dexmedetomidine as pre-anesthetic medication for the attenuation of hemodynamic changes during laparoscopic cholecystectomy surgeries. Materials and Methods: Eighty patients of either sex, aged 20–50 years, complying to the American Society of Anesthesiologists physical status I-II, scheduled for elective laparoscopic cholecystectomy under general anesthesia were divided into two equal groups to receive either clonidine 1 mg/kg (Group-C, n=40) or dexmedetomidine 1 mg/kg (Group-D, n=40), both injected through intravenous route as 15 mL volume with normal saline. Heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and SpO2 were measured before and after giving the study drugs, before and immediately after pneumoperitoneum, and then, at 10, 20, 30, 40, and 50 min of pneumoperitoneum. Results: Statistically significant difference was observed in heart rate in the dexmedetomidine group constantly since giving study drug, immediately after the creation of pneumoperitoneum, and then, 10, 20, 30, 40, and 50 min after pneumoperitoneum. Systolic, diastolic, and mean blood pressures were found to be significantly lower in Group D (except after administering study drug), immediately after creating pneumoperitoneum, and 10, 20, 30, 40, and 50 min after pneumoperitoneum. Conclusion: Dexmedetomidine as pre-medication is more efficacious in attenuating hemodynamic stress responses in laparoscopic cholecystectomy surgeries compared to clonidine as pre-medication.